Dissemination of interactive digital physics modules (IDMP) to improve teachers' Scientific Inquiry Literacy (SIL) in depth learning - Wibowo, Firmanul Catur; Nasbey, Hadi; Darman, Dina Rahmi; Hamidah, Iffah; Prasetiyo, Thomas Enggar Dwi; Steeven, Daniel; Mahmuda, Muhammad Suryauno; Yacobi, Muhammad Abrar Asyrafy; Agustino, Rinto; Arymbekov, Beken (Education and Development Research, 2025)
The Background of study is strengthening Scientific Inquiry Literacy to a critical urgency to equip the younger generation with logical, analytical, and evidence-based thinking skills to face complex challenges in the 21st century. The study objective examines the dissemination of the Interactive Digital Module Physics (IDMP) in improving teachers’ Scientific Inquiry Literacy (SIL) in immersive learning. The of study of method Through a mixed-methods approach with 55 science teachers in Jakarta, Indonesia aged 35-55 years as participants, data were collected through the SIL pretest-posttest and implementation observations. The results showed an adoption rate of 83.3% of the IDMP, with 73.3% of teachers successfully integrating it into their lesson plans. The implementation of the Interactive Digital Module Physics (IDMP) led to a significant improvement in teachers’ scientific inquiry literacy, with N-Gain scores of 25%, 23%, and 22% in designing investigations, guiding inquiry, and evaluating scientific processes, respectively. The implication of study for demonstrate the effectiveness of the IDMP in supporting immersive learning through interactive simulation features. The development of collaborative features such as discussion forums and experimental data banks is recommended to facilitate ongoing practice among teachers.